Influence of Carbon Nanotubes in Improving the Superconducting and Structural Properties of Bulk Bi-2212 Synthesis by Thermal Treatment Method - Sukor, Safia Izzati Abd; Kechik, Mohd Mustafa Awang; Kamarudin, Aliah Nursyahirah; Shaari, Abdul Halim; Kien, Chen Soo; Pah, Lim Kean; Shariff, Khairul Khaizi Mohd; Shabdin, Muhammad Kashfi; Yaakob, Yazid; Karim, Muhammad Khalis Abdul; Doyan, Aris (Balai Publikasi Indonesia, 2024)
Bi-2212 superconductor has garnered significant interest in recent years due to its potential applications in the development of superconducting wires and tapes. The effect of introducing carbon nanotubes (CNT) into the Bi-2212 system was investigated in terms of superconducting and structural properties. The results of this study indicated that the addition of CNTs had a notable effect on the phase formation of Bi-2212, with a substantial increase from 86.8% to 97.4% for the sample with a weight percentage of 0.8 wt.%. This can be attributed to the improved particle orientation brought about by the introduction of CNTs. The microstructure analysis displayed randomly distributed grains of irregular shapes, with a reduced average grain size of 1.018 μm upon the addition of 0.4 wt.% CNTs. Additionally, the inclusion of CNTs led to an increase in the Tc value, with the maximum Tc-onset recorded at 79 K for the sample containing 0.6 wt.% CNTs. In summary CNT has enhanced the structural and the superconducting properties of the Bi-2212 synthesised with thermal treatment method.